EXCLUSION OF LIABILITY OF SERVICE PROVIDERS FOR OFFENSIVE CONTENT IN THE CASE LAW OF THE EUROPEAN COURT OF HUMAN RIGHTS - Wątor, Weronika (Człowiek w cyberprzestrzeni, 2020)
In the internet age, offensive content is becoming more and more common online. Entries containing phrases that violate the good name of third parties appear both in Internet forums and in comment sections of websites or blogs. This phenomenon is difficult to combat, as these contents are most often published by anonymous users. Accordingly, a person who believes that his or her good name has been damaged is faced with the problem of establishing the identity of a person whom they could hold accountable. It is therefore often the case that responsibility is placed on the Internet intermediary, the entity that has allowed the use of the medium in question. The paper is to present measures to be pursued by Internet intermediaries in order for their liability for offensive content to be excluded. The content of this article derives from the review of the binding legislation and judicial decisions of the ECHR.